Projection and Resources Adjustment in Cassava Production in Oyo State, Nigeria - Olaniyi, Olayiwola O (Review of Knowledge Economy, 2015)
Projection was made by the use of ARIMA model, contribution of area and yield towards cassava production was done by decomposition analysis and adjustment in cropping pattern was estimated by calculating index level. Forecast result showed that maximum value of area is 843.0 thousand hectares which would be expected in 2013-14 while minimum value is 826.0 thousand hectares which is likely to occur by the year 2025-26. Production forecast revealed maximum value of 1407.0 thousand tons which would be expected by 2025-26 and the minimum value of 1181.0 thousand tons in 2012-13.